Cohort profile: the Funen Diabetes Database—a population-based cohort of patients with diabetes in Denmark - Reimar Wernich Thomsen; Henrik Toft Sørensen; Jan Erik Henriksen; Lars Pedersen; Kasper Adelborg; Péter Szentkúti; Jens Sundbøll; Ole Hother-Nielsen; Henning Beck-Nielsen (BMJ Open)
Purpose Detailed population-based data are essential to understanding the epidemiology of diabetes and its clinical course. This article describes the Funen Diabetes Database (FDDB). The purpose of the FDDB was to serve as a shared electronic medical record system for healthcare professionals treating patients with diabetes. The cohort can also be used for research.Participants The FDDB covers a geographical area of almost 500 000 Danish inhabitants. It currently includes 3691 patients with type 1 diabetes, 19 085 patients with type 2 diabetes, 292 patients with other types of diabetes and 5992 patients with an unknown type of diabetes. Patients have been continuously enrolled from general practitioners and endocrinology departments in the Funen area in Denmark since 2003. Patients undergo a clinical work-up at their first diabetes contact and during follow-up visits. The information collected includes type of diabetes contact, blood pressure, height, weight, lifestyle factors (smoking, exercise), laboratory records (eg, haemoglobin A1c and cholesterol levels), results from foot examinations (eg, pulse, cutaneous sensitivity and ankle brachial index), results from eye examinations (eg, degree of retinopathy assessed by retinal photo and eye examination), glucose-lowering drugs and diabetic complications.Findings to date The FDDB cohort was followed for a total of 212 234 person-years up to 2016. A cross-sectional study described the prevalence of diabetic retinopathy and its associated risk factors. The clinical outcomes of patients with type 1 diabetes, type 2 diabetes and latent autoimmune diabetes in adults have been assessed. Linkage to population-based medical registries with complete follow-up has enabled the collection of extensive continuous data on general practice contacts, diagnoses and procedures from hospital contacts, medication use and mortality.Future plans The FDDB serves as a strong data resource that will be used in future studies of diabetes epidemiology with focus on occurrence, risk factors, treatment, complications and prognosis.